Profits from Forward Exchange Speculation - Grubel, Herbert G. (Quarterly Journal of Economics, 1965)
I. Speculators as suppliers of forward exchange, 248. — II. The model, 251. — III. Data, behavioral assumptions and results, 254. — IV. Interpretations of computations, 258. — V. Implications for forwawrd exchange supply, 260.